The Analysis of the Seasonal Changes of Microbial Communities in the Activated Sludge of Small and Large Wastewater Treatment Plants - Sipos, Dóra; Miseta, Roland; Zseni, Anikó (International Journal of Engineering and Management Sciences, 2018)
In our research the seasonal changes of the microbial communities in the activated sludge of one large and two small wastewater treatment plants are observed and analysed. During the research, 14 months of data were processed. After the sample analysis and data processing, the research revealed the efficiency of the ecological system, and also showed the seasonal changes of the community structures. The results of the statistical analysis show, that the seasonality is less observable in the case of the larger system. Presumably, the larger bioreactors have more stable microbial composition. In addition, we searched for more connections between the components of the ecological system, the changing in the weather, and also in the efficiency in the process for treating wastewater.